Labour with low dose epidural analgesia: maternal perception and fetal outcome - Sawant, Vasudha; Kumbhar, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Experiencing labour pains and giving birth to infant is normal physiological process. Though it is a natural phenomenon, it produces severe pain which requires analgesia to relieve pain during labour. The objective of this study was to compare effects of low dose epidural analgesia verses no analgesia during labour on mother and fetus. Methods: Here in this study we have assessed effect of epidural analgesia on mother and fetus. Total we have taken 60 women in age group of 20-26 years with full term pregnancy (37-42 weeks). Those who have entered spontaneous labour with vertex presentation, without any previous uterine surgery, clinically adequate pelvis. We had divided these women in 2 groups, 30 were given epidural analgesia and 30 without any analgesia. Variables recorded were pain score during labour using VAS, duration of labour during each stage, mode of delivery, Apgar score of newborn at 1 minute and 5 minutes. Results: Present study shows that duration of first stage of labour in epidural and non-analgesia group are same. Second stage of labour is prolonged in epidural group than non-analgesia group. Both groups had normal APGAR score. Epidural analgesia is not associated with any change in mode of delivery. Visual analogue scale is good with epidural analgesia. Conclusions: There was no significant difference in first stage of labour in both group. Second stage of labour was slightly prolonged in EA group than control, but it was less than two hours. No harmful neonatal outcome in epidural analgesia.